Novel insights into the regulation of exosomal PD-L1 in cancer: From generation to clinical application - Liu, Jie; Qin, Junxia; Liang, Lili; Zhang, Xinzhong; Gao, Jie; Hao, Youwei; Zhao, Peng (European Journal of Pharmacology, 2024)
Programmed cell death ligand 1 (PD-L1) interacts with programmed cell death 1 (PD-1), leading to T cell exhaustion and promoting tumor cell survival, ultimately mediating immunosuppression. While FDA-approved monoclonal antibodies targeting the PD-1/PD-L1 interaction have shown success in cancer treatment, some patients experience limited and short-lived therapeutic outcomes. Recent studies have identified PD-L1 expression not only on tumor cell surfaces but also on exosomes, with secretion pathways including both conventional and unconventional endocytosis routes, presenting a unique therapeutic opportunity. Emerging evidence suggests that exosomal PD-L1 contributes to systemic immunosuppression, potentially counteracting the effects of anti-PD-1 checkpoint therapies. However, the significance of exosomal PD-L1 in clinical cancer patients unresponsive to anti-PD-1/PD-L1 immunotherapy, as well as the factors regulating its generation, remain unclear. Moreover, the mechanisms underlying PD-L1 expression on exosomes and its regulation in cancer are yet to be fully elucidated. This review primarily focuses on the mechanisms modulating exosomal PD-L1 generation in cancer, while also outlining its involvement in immunosuppression, tumor proliferation, and response to cancer immunotherapy. Additionally, we explore the potential of exosomal PD-L1 as a cancer biomarker and therapeutic target, aiming to provide a comprehensive overview of this emerging field and its implications for cancer treatment and diagnosis.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Biomarker; Exosome; Generation; PD-L1; Therapeutic target